Controlled release kinetics of furosemide from chitosan matrix tablets with hydroxypropyl methylcellulose phthalate coated - Samran, Samran; Suprianto, Suprianto; Sumardi, Sumardi; Ritonga, Ahmad Hafizullah; Kusumastuti, Melati Yulia (Universitas Ahmad Dahlan, 2024)
Sustained-release dosage forms were critical in drug delivery, ensuring controlled and prolonged release for optimal therapeutic outcomes. Chitosan (CH) has become pivotal in sustained-release tablet formulation due to its biocompatibility and mucoadhesive properties. This study aims to explore the release kinetics of furosemide (FS) from CH matrix tablets in a concurrent medium. The formulation involves a core tablet and coated tablet, with CH matrix as a binder and Hydroxypropyl Methyl Cellulose Phthalate (HPMCP) as a film-coated for the core tablet, and both are made using the wet granulation method. Assessment parameters include tablet hardness, disintegration, and FS release profiles across various media, analyzed using spectrophotometric methods to comprehend drug release kinetics with multiple models such as zero-order, first-order, Higuchi, and Korsmeyer-Peppas employed. In the press-coated tablet comprising core tablet CH as matrix uncoated with 20 mg CH per tablet core, a zero-order release pattern emerged in the pH 1.2 medium within 0-2 h, which displayed first-order release kinetics within 2-6 h and 6-16 h in concurrent media of pH 5.8 and 7.4. Notably, a zero-order release pattern emerged in the pH 1.2 medium within 0-2 h. Press-coated tablets incorporating CH matrix with HPCMP coated (CH-HPCMP), also containing 20 mg CH per tablet, exhibited diverse drug release kinetics. These tablets showed Korsmeyer-Peppas, zero-order, and first-order kinetics in pH 1.2, 5.8, and 7.4, respectively. The study suggests that a Press-coated tablet incorporating CH-HPMCP is suitable as the candidate for sustained-release formulations. The observed versatility in release kinetics across varying pH environments underscores the potential adaptability of these formulations in addressing diverse therapeutic needs.